HUBUNGAN TINGKAT KECEMASAN DENGAN TEKANAN DARAH ANGGOTA PROLANIS DI PUSKESMAS PARONGPONG - Meike Mercy Coloay; Imanuel Sri Mei Wulandari (Jurnal Kesehatan, 2020)
Hypertension is a problem arising in every health service in Indonesia, with more than 25% of cases. Hypertension itself has two risk factors that can be changed and cannot be changed. The increasing age of hypertension is an irreversible factor, while psychological problems are factors that can be changed. The method used in this research is quantitative descriptive correlation with cross-sectional approach. Respondents in this study are all Prolanis members who actively participate in activities at least once a month, which is 40 respondents. The spearman rho test is used in analyzing the relationship of two variables. The results obtained from this study are respondents have moderate anxiety levels and systolic and diastolic blood pressure shows the category of moderate hypertension. Correlation test to get results there is a significant relationship between anxiety levels with blood pressure with a value of p <0.05. It is recommended for respondents to pay attention to changes in blood pressure when experiencing changes in psychological problems, and be able to participate in prolanis activities to get emotional support